Digital Design and Manufacturing Technology II : Selected, peer reviewed papers from the 2011 Global Conference on Digital Design and Manufacturing Technology, January 23rd-25th, 2011, Hangzhou City, Zhejiang Province, P.R. China (Advanced materials research ;, 2011)
The rapid growth in digital design and manufacturing processes brings with it some work-flow challenges. While the various existing products provide an ideal solution to most of the steps in the process, more dedicated and integrated systems are sometimes required; raising the question of how best to handle the incoming data and orders, automate the design and possibly the engineering, make robust plans, manage the process and data and deliver quality goods. This collection of peer-reviewed papers on digital design and manufacturing technology explains the ins-and-outs of CAD/CAM technologies and how these tools can be used to model and manufacture building components and industrial design products. It offers a comprehensive overview of the field and expertly addresses a broad range of recent initiatives and other issues related to the design of parts for manufacturing and assembly; including the broad range of software, computerized numerical control machines, programming, manufacturing processes and prototyping required. This book will provide a valuable and fruitful reference source for researchers in the fields of digital design and manufacturing who wish to understand further the underlying mechanisms and to create new and practical design technologies, systems and processes. Review from Book News Inc.: Selected and peer-reviewed, the 81 papers gathered in this volume look at the current status of computer-aided design and manufacturing of components and products. The topics include cutting forces in helical milling processes, methods for evaluating uniformity in the lapping process, applying visualization in scientific computing technology, the numerical and flow-field simulation of acoustic levitation polishing, designing cold extrusion dies for precision gears, applying ultrasonic radiation forces, the impact of plate cylinder deformation on graphic quality, and the autonomous control of abrasive flow precision machining.